Implementasi Sistem Pendukung Keputusan menggunakan Metode Simple Multi Attribute Rating Technique (SMART) untuk Seleksi Penerimaan Siswa Baru - Jayusman, Yus (Jurnal Bangkit Indonesia, 2025)
The admission of new students is a crucial process for schools to select prospective students who meet predefined criteria. Currently, the selection process at SMA Bina Muda Cicalengka is still conducted manually, which increases the risk of errors and inefficiencies. Therefore, a more modern and structured student admission selection system is required. This study aims to develop a Web-Based Decision Support System for New Student Admission Selection to facilitate the registration process, enhance selection accuracy, and provide more systematic data for in-depth analysis. The system employs the Simple Multi-Attribute Rating Technique (SMART) to evaluate prospective students based on several criteria, such as the average diploma score, academic achievements, and economic background. The development process follows the Extreme Programming (XP) methodology, enabling a more flexible and adaptive approach to user requirements. The research findings indicate that implementing a web-based system at SMA Bina Muda Cicalengka allows for broader accessibility and generates a faster and more optimal selection process. The integration of information technology in the student admission selection process has proven to enhance transparency and fairness, thereby improving the school's decision-making quality and overall service efficiency.